Determinants of diarrhoeal infections among users of shared sanitation in informal settlements in Durban, South Africa. (29th August 2022) - Ramlal, Preshod Sewnand; Lin, J.; Buckley, C. A.; Stenström, T. A.; Amoah, I. D.
Abstract: Diarrhoeal disease continues to be a major health problem in many parts of the world, especially in developing countries, mainly due to the lack of access to sanitation, water, and hygienic living conditions. Identifying the determinants of diarrhoeal infections continues to be a challenge in developing countries. In this study, we ascertained the factors behind diarrhoea among inhabitants of informal settlements in the city of Durban, South Africa. Prevalence of diarrhoea in the study area varied between 7-year historical clinical records and data collected during the current study (primary data), with the primary data giving the highest monthly prevalence odds ratio (POR) up to 18.1 (±1.6)%. The main factors associated with diarrhoeal infections were open defaecation (POR = 1.8; 95% confidence interval (CI): 0.9–3.12), use of shared sanitation (POR = 1.7; 95%; CI: 1.05–2.26), and exposure to faecal matter around the homes (POR = 1.69; 95% CI: 1.25–3.10). Several other factors were also determined to be associated with diarrhoeal infections, such as hygiene practices in the communities, the non-treatment of water before use, and the presence of solid waste and faecal materials around the households. This study shows that diarrhoeal disease infections in informal settlements could be multifactorial; therefore, a multifactorial approach is needed to reduce these infections. These could include improving education on hygiene practices within the home setting as well as in public places, such as the community ablution blocks. HIGHLIGHTS: Prevalence of diarrhoea in informal settlements in South Africa is high compared to the national diarrhoeal prevalence. The main factors associated with increased risks of diarrhoea included the use of these community ablution blocks (CABs), poor hygiene, open defaecation, use of communal water, and poor household conditions. There was no spatial relationship between the high diarrhoeal cases in households and the location of the CABs. Graphical Abstract